Inflation and Cross-National Homicide: Assessing Nonlinear and Moderation Effects Across 65 Countries, 1965–2015 - Rennó Santos, Mateus (International criminal justice review, 2021)
Criminologists have long speculated that economic conditions play a role in driving crime trends. Emerging research finds that inflation rates are associated with crime rates both within the United States and cross-nationally. Inflation is hypothesized to increase crime by incentivizing illegal markets and organized criminal activity and by reducing the legitimacy of social institutions. Existing research on the association between inflation and homicide rates has been limited to single-country studies or multicountry studies consisting of developed countries only. Moreover, there has been limited attention to the potential complexity of this relationship, including whether it is nonlinear, as crime rates may only increase after a certain threshold of inflation is reached, and whether the criminogenic impact of inflation may be moderated by socioeconomic development, as developing countries are anticipated to be more adversely impacted by the criminogenic influence of inflation. Drawing on a sample of 65 economically diverse countries from 1965 to 2015, we find a positive direct relationship between inflation and homicide rates, although we do not find evidence that this association is nonlinear. Finally, contrary to expectation, we find that the inflation–homicide relationship is most impactful in countries with higher levels of development. We discuss these findings in the context of cross-national predictors of crime.